(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The subject of the international responsibility has been subjected to major developments that has led to its expansion. Traditional theories that were the basis for building the idea of international responsibility are no longer applicable today. Scientific progress and industrial development have been accompanied by serious cross-border damages and their effects may not appear in the short term, making it very difficult to prove these damages. Certain countries have also taken legitimate actions without attributing any mistake to its benefit, but they are harming other countries. This has made the subject of the international responsibility a necessity among jurists because of its importance in international relations. One of the most prominent theories on which international responsibility was founded and applied in the judiciary and international arbitration is the theory of error, the theory of unlawful action and the theory of risks.